Islamic Law and Ethics - Vishanoff, David R. (International Institute of Islamic Thought, 2020)
Does Islamic law define Islamic ethics? Or is the law a branch of a broader ethical system? Or is it but one of several independent moral discourses, Islamic and otherwise, competing for Muslims' allegiance? The essays in this book present a range of answers: some take fiqh as the defining framework for ethics, others insert the law into a broader ethical system, and others present it as just one among several parallel Islamic ethical discourses, or show how Islamic ethics might coexist with non-Muslim normative systems. Their answers have far reaching implications for epistemology, for the authority of jurists and lay Muslims, for the practical moral challenges of daily life, and for relationships with non-Muslims. The book presents Muslim ethicists with a strategic contemporary choice: should they pursue a single overarching methodology for judging all ethical questions, or should they relish the rhetorical and political competition of alternative but not necessarily incompatible moral discourses?